From cationic ring-opening polymerization to atom transfer radical polymerization - Matyjaszewski, K. (Polimery, 2014)
Roots of controlled radical polymerization, including atom transfer radical polymerization (ATRP), originate in living ionic polymerizations accompanied by reversible deactivation, such as cationic ring-opening polymerization of tetrahydrofuran and other heterocyclics. Recent developments in ATRP, including mechanistic understanding, synthesis of polymers with precisely controlled architecture and some applications of polymers prepared by ATRP are presented.